PERAN STANDAR AKUNTANSI KEUANGAN SYARIAH DALAM MENINGKATKAN KUALITAS PENYAJIAN LAPORAN KEUANGAN - Marheni Marheni (Budgeting: Jurnal Akuntansi Syariah, 2022)
Islamic financial institutions, whether bank or non-bank, in the process of presenting financial statements must refer to Islamic financial accounting standards so that the resulting financial reports are of high quality. The purpose of this paper is to determine the role of Islamic financial accounting standards in improving the quality of financial statement presentation. The conclusion obtained from the discussion of this article is that every financial institution with sharia principles must understand sharia financial accounting standards. In order to present quality financial reports, Islamic financial institutions can be guided by PSAK sharia 101. With a good and correct understanding of PSAK sharia 101, the presentation of the company's financial statements will be structured, accountable, easy to understand, relevant, comparable and reliable